A kognitív készségek hatása a diplomások bérére - Anna Sebők (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– This paper investigates the role of cognitive skills in the return to higher education (HE) in Hungary. It makes use of linked Hungarian administrative data, which contains labor market and educational information of about 50 percent of the Hungarian population, for the period of 2003 and 2017 (Sebîok 2019). The estimates are focused on the early carrier path of HE graduates who completed their National Assessment of Basic Competencies 10th class tests in 2008. The paper uses Mincertype regression modells with the test scores as the the proxy variables of cognitive skills.
Keywords: I23; 330; competences; HE return; tracking; cognitive skills